2016
DOI: 10.1242/jeb.149237
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of cardiac output is overcome by adrenergic stimulation in the anaconda heart

Abstract: Most vertebrates increase cardiac output during activity by elevating heart rate with relatively stable stroke volume. However, several studies have demonstrated 'intrinsic autoregulation' of cardiac output where artificially increased heart rate is associated with decreased stroke volume, leaving cardiac output unchanged. We explored the capacity of noradrenaline to overcome autoregulation in the anaconda heart. Electrically pacing in situ perfused hearts from the intrinsic heart rate to the maximum attainabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…In perfused crocodile hearts, Axelsson and Franklin (1995) reported that adrenaline evokes a concentration-dependent tachycardia, accompanied by a proportional decrease in V S , leaving _ Q sys unchanged. It was therefore unexpected that adrenaline clearly elicits a sustained increase in _ Q sys , despite a prominent tachycardia in anaconda hearts perfused under similar conditions (Joyce et al, 2017). This is, nevertheless, reminiscent of the mammalian response (Sarnoff, 1955).…”
Section: The Regulation Of Cardiac Functionmentioning
confidence: 93%
See 1 more Smart Citation
“…In perfused crocodile hearts, Axelsson and Franklin (1995) reported that adrenaline evokes a concentration-dependent tachycardia, accompanied by a proportional decrease in V S , leaving _ Q sys unchanged. It was therefore unexpected that adrenaline clearly elicits a sustained increase in _ Q sys , despite a prominent tachycardia in anaconda hearts perfused under similar conditions (Joyce et al, 2017). This is, nevertheless, reminiscent of the mammalian response (Sarnoff, 1955).…”
Section: The Regulation Of Cardiac Functionmentioning
confidence: 93%
“…In many species, including fish, reptiles and mammals, increasing myocardial contractility with adrenaline (such as occurs during exercise) shifts the Starling curve upwards (Fig. 2, red curve), thereby elevating maximum _ Q sys (Graham and Farrell, 1989;Joyce et al, 2017;Sarnoff, 1955). However, some species exhibit a blunted inotropic response to adrenaline (Axelsson and Franklin, 1995;Farrell et al, 2007).…”
Section: The Regulation Of Cardiac Functionmentioning
confidence: 99%
“…Because input and output pressures were controlled in tandem, input pressure was calculated as the average of right and left atrial input pressures and output pressure was calculated as the average of pulmonary artery and right aortic pressures (Farrell et al, 1994;Joyce et al, 2017). Total cardiac output was defined as the sum of pulmonary and right aortic blood flow and normalised to body mass.…”
Section: In Situ Perfused Heartsmentioning
confidence: 99%
“…In their study, the decrease in filling time presumably reduced cardiac preload (e.g. Altimiras and Axelsson, 2004), which, in the absence of pronounced inotropic effects (see Joyce et al, 2017a), was likely responsible for the decrease in V S . However, in the intact circulatory system of the anesthetized alligators, adrenaline also exerts direct effects on vascular capacitance.…”
Section: Resultsmentioning
confidence: 86%